Matlab/Simulink simulation model of photo-diesel power supply system with intelligent control - B. V. Lukutin; D. I. Muravyev (Омский научный вестник)
In this article, a simulation model of an autonomous PVdiesel power supply (PDPS) system with direct current is considered. The autonomous PDPS is implemented in the Simulink programming environment of the Matlab software package. The system includes: a photovoltaic power station (PPS), a diesel generator (DG), an energy storage system (ESS), a remote consumer as well as auxiliary converters. The PDPS model makes it possible to analyze the energy balance between generation, consumption, and the energy exchange available from the ESS connected via a DC bus (DCB). With the help of the proposed model, it is possible to analyze and optimize the technical and economic indicators of DC power plants with the priority of the PPS contribution: reducing the consumption of diesel fuel and carbonation of the air reducing the cost of 1 kWh for the remote consumer and controlling the switching in the power plants as per logical conditions. The obtained technical and economic indicators of the PDPS using direct current are superior to similar systems based on alternating current due to an increase in the contribution of the PPS to the energy balance. As a result of experiments with changing input conditions, i.e. annual changes in insolation and temperature at different latitudes, the authors justify technical, economic, and environmental criteria for the effectiveness of decision-making and recommendations for the design and operation of PDPS power plants. Intelligent algorithms for effective control of PV-diesel power systems based on DC are developed and suggested.